Association of vitamin E intake at early childhood with alanine aminotransferase levels at mid‐childhood. Issue 4 (1st March 2018) - Woo Baidal, Jennifer A.; Cheng, Erika R.; Rifas‐Shiman, Sheryl L.; Oken, Emily; Gillman, Matthew W.; Taveras, Elsie M.
Abstract : The extent to which vitamin E (alpha‐tocopherol) intake early in childhood is associated with alanine aminotransferase (ALT) level later in childhood is unknown. The objective of this research is to test the hypothesis that higher alpha‐tocopherol intake during early childhood is associated with lower odds of elevated ALT levels during mid‐childhood and to examine how body mass index (BMI) influences these relationships. We studied 528 children in Project Viva. Mothers reported child dietary intake at early childhood visits (median 3.1 years) using a validated food frequency questionnaire. At mid‐childhood (median 7.6 years), we collected child blood and anthropometric data. The main outcome was elevated sex‐specific mid‐childhood ALT level (≥22.1 U/L for female children and ≥25.8 U/L for male children). In multivariable logistic regression models, we assessed the association of energy‐adjusted alpha‐tocopherol intake with ALT levels, adjusting for child age, sex, race/ethnicity, diet, and age‐adjusted sex‐specific BMI z‐score at mid‐childhood. Among children in this study, 48% were female, 63% were non‐Hispanic white, 19% were non‐Hispanic black, and 4% were Hispanic/Latino. Mean alpha‐tocopherol intake was 3.7 ± 1.0 mg/day (range, 1.4‐9.2) at early childhood. At mid‐childhood, mean BMI z‐score was 0.41 ± 1.0 units and 22% had an elevated ALT level. In multivariable‐adjusted logistic regression models, children with higher early childhood vitamin E intake had lower odds of elevated mid‐childhood ALT (adjusted odds ratio [AOR], 0.62; 95% confidence interval [CI], 0.39, 0.99) for quartiles 2‐4 compared with the lowest quartile of intake. Findings persisted after accounting for early childhood diet (AOR, 0.62; 95% CI, 0.36, 1.08) and were strengthened after additionally accounting for mid‐childhood BMI z‐score (AOR, 0.56; 95% CI, 0.32, 0.99). Conclusion : In this cohort, higher early childhood intake of alpha‐tocopherol was associated with lower odds of elevated mid‐childhood ALT level. (Hepatology 2018;67:1339‐1347).